In vitro activities of aztreonam, piperacillin, and ticarcillin combined with amikacin against amikacin-resistant Pseudomonas aeruginosa and P. cepacia isolates from children with cystic fibrosis. - Aronoff, S C (1984)
Amikacin, combined with aztreonam, piperacillin, or ticarcillin, synergistically inhibited amikacin-resistant sputum isolates of Pseudomonas aeruginosa and P. cepacia from children with cystic fibrosis. Ticarcillin-amikacin was the least active combination. Aminoglycoside resistance should not preclude the use of beta-lactam-aminoglycoside combinations in the treatment of pulmonary infections in cystic fibrosis.